Concept of the culture of Dagestan citizens in varieties of ethnic nominations - Shikhalieva, Sabrina Kh.; Abdurakhmanova, Pasikhat Ja.; Gasanova, Sapiyat Kh.; Shakhbanova, Juma N.; Peri T. Radzhabova, Helen Z. Santueva (Opción, 2019)
The study aim is to investigate the concept of culture of Dagestan citizens in varieties of ethnic nominations. On the basis of urban social dialects, the methodology for modeling of dialect groups of linguistic view of the region is interpreted. The analysis of the urban language concepts, included in the procedure for describing the worldview conception, reveals the context with the logical and sublogical marker of the speaker. As a conclusion, the constant flow of national dialect speakers into the cities of the Republic of Dagestan provides a close connection with the speech idioms of various villages.